2019
DOI: 10.3390/jof5030063
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in CD4+, CD8+ T Cell Phenotype and Activation Marker Expression Following Antiretroviral Therapy Initiation among Patients with Cryptococcal Meningitis

Abstract: Despite improvement in the prognosis of HIV/AIDS (human immunodeficiency virus/acquired immune deficiency syndrome) patients on antiretroviral therapy (ART), cryptococcal meningitis (CM) still causes 10–15% mortality among HIV-infected patients. The immunological impact of ART on the CD4+ and CD8+ T cell repertoire during cryptococcal co-infection is unclear. We determined longitudinal phenotypic changes in T cell subsets among patients with CM after they initiated ART. We hypothesized that ART alters the clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…24 Another study at the same timing reported PD-1 expression on T cells at 60% of CD4 + T cells and 30% of CD8 + T cells with persistant high PD-1 expression on circulating T cells beyond 12 weeks of follow-up. 99 In this case, it is not clear whether sustained PD-1 expression in cryptococcosis is due to persistent activation or another mechanism. But, whether PD-1 or its ligand expression is different with infecting Cryptococcus species is yet to the investigated.…”
Section: Centr Al Nervous Sys Tem Immune Ac Tivati On and Infl Ammamentioning
confidence: 95%
See 1 more Smart Citation
“…24 Another study at the same timing reported PD-1 expression on T cells at 60% of CD4 + T cells and 30% of CD8 + T cells with persistant high PD-1 expression on circulating T cells beyond 12 weeks of follow-up. 99 In this case, it is not clear whether sustained PD-1 expression in cryptococcosis is due to persistent activation or another mechanism. But, whether PD-1 or its ligand expression is different with infecting Cryptococcus species is yet to the investigated.…”
Section: Centr Al Nervous Sys Tem Immune Ac Tivati On and Infl Ammamentioning
confidence: 95%
“…One study at cryptococcal meningitis diagnosis reported the PD‐1 expression on circulating cellular lineages at 2% of B cells (CD19 + lymphocytes), 25% of T cells and 1% of monocytes 24 . Another study at the same timing reported PD‐1 expression on T cells at 60% of CD4 + T cells and 30% of CD8 + T cells with persistant high PD‐1 expression on circulating T cells beyond 12 weeks of follow‐up 99 . In this case, it is not clear whether sustained PD‐1 expression in cryptococcosis is due to persistent activation or another mechanism.…”
Section: Central Nervous System Immune Activation and Inflammationmentioning
confidence: 99%
“…The dominant mechanism for HIV-induced immunode ciency is depletion and distortion of CD4 + T cells, and further lymphocyte defects [31,32]. Therefore, dynamic monitoring of CD4 + T cell counts is critical for HIV-positive patients [34]. In our cohort, there was no signi cant difference in baseline CD4 + T cell counts at admission between favorable outcome group and unfavorable outcome group.…”
Section: Discussionmentioning
confidence: 66%